2013
DOI: 10.1371/journal.pone.0063761
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Cooperation: Combining Kin Selection and Reciprocal Altruism into Matrix Games with Social Dilemmas

Abstract: Darwinian selection should preclude cooperation from evolving; yet cooperation is widespread among organisms. We show how kin selection and reciprocal altruism can promote cooperation in diverse 2×2 matrix games (prisoner’s dilemma, snowdrift, and hawk-dove). We visualize kin selection as non-random interactions with like-strategies interacting more than by chance. Reciprocal altruism emerges from iterated games where players have some likelihood of knowing the identity of other players. This perspective allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Experiments involving pairs of unfamiliar fish that were either full siblings or unrelated revealed that relatedness enhanced the probability of joining the social partner to collectively inspect a dangerous predator [198]. This indicates that correlated pay-offs based on both relatedness and reciprocity may positively interact [209], even if negative interactions have been demonstrated as well in a pay-to-stay scenario [36,76].…”
Section: Which Conditions Select For Reciprocity?mentioning
confidence: 98%
“…Experiments involving pairs of unfamiliar fish that were either full siblings or unrelated revealed that relatedness enhanced the probability of joining the social partner to collectively inspect a dangerous predator [198]. This indicates that correlated pay-offs based on both relatedness and reciprocity may positively interact [209], even if negative interactions have been demonstrated as well in a pay-to-stay scenario [36,76].…”
Section: Which Conditions Select For Reciprocity?mentioning
confidence: 98%
“…Kin selection and reciprocal altruism have been proposed to explain how cooperation develops (see Ale, Brown, Sullivan, 2013). Kinship can promote cooperation when the benefit to the recipient increases the evolutionary fitness of the donor (Hamilton, 1964).…”
mentioning
confidence: 99%
“…Kin-selection and reciprocal altruism are often presented as opposing alternatives to explain cooperation [see Ale et al (2013)]. Reciprocal altruism promotes cooperation when long-term benefits accrue to partners interacting repeatedly, regardless of relationship (Trivers, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…In other settings, they may benefit from cooperation, either for food (cooperative hunting in carnivores) or defense from predators [mobbing in birds (Clutton-Brock, 2009)]. Kin selection and reciprocal altruism have been proposed to explain how cooperation develops [see Ale et al (2013)]. Kinship can promote cooperation when the benefit to the recipient increases the evolutionary fitness of the donor (Hamilton, 1964).…”
Section: Introductionmentioning
confidence: 99%